2012
DOI: 10.1080/17489539.2012.745293
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based practice in speech language pathologist training of early childhood professionals

Abstract: With more children attending formal child care and limited speech language pathology resources, there is a need to consider alternate service delivery models. One such approach is clinician training of early childhood professionals (ECPs). To be appropriately targeted and efficient, training programs should be based on research evidence. This systematic review focuses on studies into which ECP skills improve child language and literacy. Databases searched were PsychINFO, Scopus, Web of Science, CINAHL, ERIC, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The 104 children in the Girolametto and Weitzman study were found to produce more language when the ECEs used all three types of language promoting strategies. More recently, a systematic review exploring ECEs' skills for promoting language and literacy development in young children identified four key skill areas: developing high-quality adult-child interactions; explicit literacy instruction; developing storytelling skills; and supporting peer-topeer interactions (El-Choueifati et al, 2012). Equipping ECEs with language stimulating strategies has also been found to facilitate the development of language skills in toddlers and preschoolers (Loeb and Armstrong, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The 104 children in the Girolametto and Weitzman study were found to produce more language when the ECEs used all three types of language promoting strategies. More recently, a systematic review exploring ECEs' skills for promoting language and literacy development in young children identified four key skill areas: developing high-quality adult-child interactions; explicit literacy instruction; developing storytelling skills; and supporting peer-topeer interactions (El-Choueifati et al, 2012). Equipping ECEs with language stimulating strategies has also been found to facilitate the development of language skills in toddlers and preschoolers (Loeb and Armstrong, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A number of educators commented on the role of the early childhood setting in supporting intervention for children with SSD, which is an increasingly prominent service delivery option (El-Choueifati et al, 2012). Some educators commented that interventions such as PFSS would be better completed by children at home and outside of the early childhood setting, but at the same time they acknowledged that this would mean children may not be able to access the intervention at all.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is only limited research evidence available that demonstrates collaborative models are effective for the ‘delivery of intervention targeting specific speech and language skills’ (Jago and Radford, 2017: 202). Collaborative intervention requires educators and SLTs to have access to the same space, which poses difficulties in many contexts due to factors such as geographic distance between the SLT and the education environment, SLTs not being employed to work within education environments, and workforce shortages (El-Choueifati et al, 2012; McAllister et al, 2011; O’Brien et al, 2006). In such cases a consultative model is often used out of necessity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to providing direct assessment and intervention, SLPs may collaborate with educators to develop classroom-based educational programmes for oral language and early literacy, and deliver professional development for educators (Speech Pathology Australia, 2011c). SLPs have been urged to support educators to develop and support high quality adult-child and peer-to-peer interactions, children's storytelling skills and explicit literacy instruction (El-Choueifati et al, 2012).…”
Section: Contributions To Oral Language and Literacy Development Within Schoolsmentioning
confidence: 99%
“…The Australian Journal of Indigenous Education facilitate development of shared understandings between SLPs who may focus on individual children with spoken language concerns and educators who focus on classroom cohorts and broader learning concerns (El-Choueifati et al, 2012). However, educators report limited training opportunities to access specialist knowledge in oral language and early literacy (El-Choueifati et al, 2012;El-Choueifati et al, 2014;Scarinci et al, 2015).…”
Section: Contributions To Oral Language and Literacy Development Within Schoolsmentioning
confidence: 99%